2022
DOI: 10.1186/s12870-022-03559-z
|View full text |Cite
|
Sign up to set email alerts
|

Machine learning models outperform deep learning models, provide interpretation and facilitate feature selection for soybean trait prediction

Abstract: Recent growth in crop genomic and trait data have opened opportunities for the application of novel approaches to accelerate crop improvement. Machine learning and deep learning are at the forefront of prediction-based data analysis. However, few approaches for genotype to phenotype prediction compare machine learning with deep learning and further interpret the models that support the predictions. This study uses genome wide molecular markers and traits across 1110 soybean individuals to develop accurate pred… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 27 publications
(14 citation statements)
references
References 56 publications
0
14
0
Order By: Relevance
“…There currently appears to be few advantages to using MLGP over LMMGP, with further improvements needed to deliver stepchange improvements in crop genetic gain. Other studies have reported similar findings where relative performance of MLGP and LMMGP has been (disappointingly) similar, highly susceptible to dataset structure and experimental design, and generally non-transferrable to new datasets (Aono et al, 2022;Danilevicz et al, 2022;Gill et al, 2022;Jubair and Domaratzki, 2023). This initial lack of progress may not yet rule out the capabilities of MLGP with further development.…”
Section: Discussionmentioning
confidence: 88%
“…There currently appears to be few advantages to using MLGP over LMMGP, with further improvements needed to deliver stepchange improvements in crop genetic gain. Other studies have reported similar findings where relative performance of MLGP and LMMGP has been (disappointingly) similar, highly susceptible to dataset structure and experimental design, and generally non-transferrable to new datasets (Aono et al, 2022;Danilevicz et al, 2022;Gill et al, 2022;Jubair and Domaratzki, 2023). This initial lack of progress may not yet rule out the capabilities of MLGP with further development.…”
Section: Discussionmentioning
confidence: 88%
“…The problem of whole-genome predictions of continuous phenotypes proves to be particularly hard to tackle for deep learning, given that state-of-the-art penalized regression models already achieve nearly optimal-predictive ability. An interesting example was provided by Gill et al 39 , who showed that other machine learning methods (i.e. random forest and XGBoost) outperformed deep learning on a soybean dataset, with the extra benefit of model interpretability and data insights.…”
Section: Discussionmentioning
confidence: 99%
“…When lecturers discuss lesson plans, things they normally have to deal with are creating an atmosphere conducive to collaboration, for example by suggesting that all lecturers be given the opportunity to express their opinions instead of being asked for them (Wahyuni, 2015). Choosing the right implementation model can have a significant impact on the efficiency and effectiveness of learning (Mulyasa, 2011;Sedgewick et al, 2016;& Gill et al, 2022).…”
Section: Discussionmentioning
confidence: 99%